Structural studies of malaria proteins - Mayer, C (2012)
Malaria is a disease of global importance, causing hundreds of thousand of deaths a year. The majority or deaths are caused by Plasmodium falciparum, a parasite transmitted by the mosquito Anopheles. Its pathogenicity largely results from an ability to transform infected erythrocytes by creating knob-like structures that result in endothelial adhesion. Two major components of these knob structures have been identified as P. falciparum erythrocyte membrane protein 1 (PfEMP1) and knob-associated histidine rich protein (KAHRP). The extracellular fragment of PfEMP1 is responsible for antigenic variability and cytoadherence while its intracellular domain (ATS) connects to the cytoskeleton via interactions with other plasmodium-encoded proteins. In addition, perforin-like proteins (PLPs) with a MACPF domain have been identified in the genome of Plasmodium. PLPs are highly conserved and are expressed in various life-cycle stages of the parasite. They are believed to form pores in membranes of the host cell but their structure is yet unknown. The aim of the work in this thesis was to obtain new information about the structure and role of malaria proteins, thus giving a better understanding of the disease and its possible treatment. Studies of numerous designed constructs of the ATS family were carried out using biophysical methods including high resolution NMR and CD. These revealed that ATS domains are mainly unstructured with a relatively small folded core, consisting of a bundle of α-helices. Surprisingly, no evidence could be found for ATS binding to KAHRP in solution conditions although previous pull-down data had indicated an interaction. Bioinformatics analysis and yeast-two-hybrid data suggested, however, that there is a conserved protein interaction epitope on the central flexible part of ATS. It was shown, using fluorescence anisotropy measurements, that this part of ATS associates with a parasite protein containing a PHIST (Plasmodium helical interspersed sub-telomeric) domain. Expression constructs of the PLP protein family were designed and manufactured, with the aim of enabling structural studies of this putative pore protein.